Nucleating Agents of Vertebrates and Invertebrates - Gulevsky, A. K.; Relina, L. I. (Problems of Cryobiology and Cryomedicine, 2011)
The information on invertebrate and vertebrate nucleating agent structure and activity is presented in the review. The data on animals' nucleators are compared with those of nucleators of bacterial origin.